The effects of an adapted physical activity program on motor performance and behaviour of children with autism spectrum disorder - Ferguson, Leanne (Stellenbosch : University of Stellenbosch, 2010)
Thesis (M Sport Sc (Sport Science))--University of Stellenbosch, 2010.